THE CORRELATION BETWEEN THE HABIT OF CONSUMING FAST FOOD AND THE INCIDENCE OF OBESITY IN ADOLESCENTS AT SMAN 15 BEKASI CITY - Abrilla, Adizha; Ernauli Meliyana; Rotua Suriany Simamora (Rena Cipta Mandiri, 2025)
Obesity is a condition where body fat is more than the energy used. Obesity can be caused by several factors, one of which is the frequency of frequent consumption of fast food. Fast food or commonly called fast food is a food that contains high sugar, low fiber as well as preservatives and coloring.This study aims to determine the correlation between the habit of consuming fast food with the incidence of obesity in adolescents at SMAN 15 Bekasi City.The research method used is quantitative with a cross sectional type of research. The population in this study were teenagers in class XI IPS at SMAN 15 Bekasi City and a sample of 92 students. The data collection technique was using simple random sampling. Statistical test using chi square test with the results of respondents who have the habit of consuming fast food (fast food) high category as many as 45 (48,9%) and respondents with obesity incidence as many as 60 (65,2%) obtained p value (0,000) < α value (0,05).There is a correlation between the habit of consuming fast food with the incidence of obesity in adolescents at SMAN 15 Bekasi City.